Nonparametric estimation of a compensating variation: The cost of disability - Ruth Hancock; Marcello Morciano; Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2013)
We propose a nonparametric matching approach to estimation of implicit costs based on the compensating variation (CV) principle. We apply the method to estimate the additional personal costs experienced by disabled older people in Great Britain, finding that those costs are substantial, averaging in the range 48-61 a week, compared with the mean level of state disability benefit (28) or total public support (47) received. Estimated costs rise strongly with the severity of disability. We compare the nonparametric approach with the standard parametric method, finding that the latter tends to generate large overestimates unless conditions are ideal. The nonparametric approach has much to recommend it.
Keywords: C81; D1; I1; 330; compensating variation; disability; matching; nonparametric